INSULIN SENSITIVITY TO TRACE METALS (CHROMIUM, MANGANESE) IN TYPE 2 DIABETIC PATIENTS AND NON DIABETIC INDIVIDUALS - Hajra, Bibi; Orakzai, Shaukat Ali; Faryal, Uzma; Hassan, Mukhtar; Rasheed, Shazia; Wazir, Salim (Journal of Ayub Medical College Abbottabad, 2016)
Background: Diabetes mellitus constitutes one of the most important problems in developing and non-developing countries. The purpose of the study to estimate the concentrations of Chromium and Manganese in diabetic and non-diabetic population of Hazara division. The cross sectional comparative study was carried out on one hundred blood samples of Type 2 Diabetic patients collected non-randomly from Ayub Teaching Hospital and one hundred normal healthy controls from Women Medical College Abbottabad from September 2014 to April 2015. Methods: The study included two hundred subjects. Among them 100 were diabetic and 100 non diabetic respectively. The blood samples were collected from Ayub Medical College, Abbottabad. The serum Chromium and Manganese levels were determined by Atomic Absorption spectrophotometer. Results: Serum Chromium and Manganese levels were decreased in diabetic and increased in non-diabetic patients. Conclusion: Low serum level of Chromium and manganese were found in diabetic patients as compare to non-diabetic individuals. Keywords: .Chromium; Manganese Atomic Absorption Spectroscopy